2021
DOI: 10.1002/suco.202100355
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of performable geopolymer mortars for use as repair material

Abstract: Heritage masonry constructions constitute an important percentage of the structures in many countries. These structures are highly vulnerable to environmental changes (such as earthquakes), and significant losses in masonry historical constructions occur even in a moderate earthquake. For this reason, damage assessment studies of these structures before earthquakes are of great importance. After an earthquake, historical buildings in Turkey were examined and it was found that many buildings underwent damage. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Every year, almost four billion tons of PC are produced, making it the dominant binder in the construction sector [9]. Consequently, it has become essential to create novel binders that use less energy to manufacture and result in lower GHG emissions [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Every year, almost four billion tons of PC are produced, making it the dominant binder in the construction sector [9]. Consequently, it has become essential to create novel binders that use less energy to manufacture and result in lower GHG emissions [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers used a rotational viscometer and stated that the yield stress of admixture‐free mixture was around 2.05 Pa which reduced to 1.85 and 1.25 Pa upon addition of the melamine‐derived synthetic polymer and modified polycarboxylic ether‐based admixtures, respectively. Maras 32 studied the viscosity of geopolymer repair mortar and stated that the viscosity of these materials was influenced by geometry, size, and volume fraction of particles. Alnahhal et al 27 on the other hand, investigated the effect of Ms ratio and solution/binder ratio on the rheology of fly ash alkali activated pastes with 20% slag replacement, and reported that the yield stresses ranged from approximately 0.10 to 0.70 Pa.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical investigation included sample testing using UPV and SRH to estimate the GPC compressive strength along with the compression test. The mixing proportions and testing results for collected from Muslum's study are listed in Table 3 [11]. The relationship between the CS of the GPC samples and the above-mentioned test results are presented in Fig.…”
Section: Muslum [11]mentioning
confidence: 99%
“…The GPC uses pozzolanic materials high in alumina and silica content as a NDTs such as the Ultrasonic Pulse Velocity (UPV) and the Schmidt Rebound Hammer (SRH) to forecast the CS of GPC. These studies reviled that, as in conventional concrete, there are correlations between the GPC CS and both RN and UPV [10,11]. Many NDTs are combined and frequently used empirically, yet, owing to the limited number of existing NDTs, they were seen to be inaccurate.…”
Section: Introductionmentioning
confidence: 99%